Reimagining Urban Public Spaces through Human-Centered Spatial Design in Growing Coastal Cities - Riko Londah (Jurnal Ragam Pengabdian, 2026)
The rapid growth of the coastal area of Manado City, especially in the Malalayang Beachfront and Boulevard Area, raises an urgent need to redesign public spaces that are more inclusive, adaptive, and in accordance with the dynamics of the rapidly changing coastal environment. Public spaces in these two areas have a high intensity of activity and are undergoing various revitalization processes so that they demand a design approach that is centered on user experience and needs. This study aims to formulate a model of redesigning coastal public spaces based on human-centered spatial design by examining space use patterns, user needs, and spatial characteristics that affect the quality of spatial experience. Using a Design-Based Research approach combined with Human-Centered Design, this study involves observation of user behavior in coastal public spaces as well as semi-structured interviews with a number of informants representing space users, business actors, area managers, and related stakeholders. Data are analyzed through thematic reduction and spatial mapping to identify key design issues and opportunities. The results of the study show that the quality of public space in Malalayang and the Boulevard Area is influenced by the connectivity of pedestrian paths, the comfort of the microclimate, the intensity of social activities, and the capacity of space in responding to coastal ecological conditions. The design findings affirm the importance of the integration of shaded spaces, experiential pedestrian path configurations, easily accessible social interaction areas, and adaptive elements that support coastal resilience. This study concludes that the DBR and HCD approaches are able to produce more responsive, inclusive, and sustainable coastal public space design, and make an important contribution to the development of coastal urban design theory and public spatial planning practices in growing coastal areas